Contribution to the biology of Coleophora namaqua Baldizzone & van der Wolf, 2015 from South Africa (Lepidoptera: Coleophoridae) - Thomas Kaltenbach; Giorgio Baldizzone (SHILAP)
Larvae of Coleophora namaqua Baldizzone & van der Wolf, 2015 were collected on their foodplant and reared to imagines. It is the first documented breeding of a Coleophora Hübner, 1822 species from South Africa. The larval case is described, and COI sequences were obtained. Further, variations in male and female genitalia are briefly discussed and illustrated.